Governance and service delivery Practical applications of social accountability across sectors - Wetterberg, Anna; Brinkerhoff, Derick W.; Hertz, Jana C. (RTI Press Publication, 2016)
RTI International has extensive experience implementing international donor-funded programs and projects, including single-sector and multisector policy and service-delivery improvement efforts, as well as governance and public management reforms. Drawing on that experience, this collection examines six recent RTI International projects, funded mostly by the United States Agency for International Development, that pursued several different paths to integrating service delivery and governance through engaging citizens, public officials, and service providers on issues related to accountability and sectoral services. The six cases illustrate the multiple ways in which citizen participation in accountability, called social accountability, can lead to positive effects on governance, citizen empowerment, and service delivery. The analysis focuses on both the intended and actual effects, and unpacks the influence of context on implementation and the outcomes achieved.